(untitled) (Connessioni remote. Artivismo_Teatro_Tecnologia, 2024)
If voice is pure situated and embodied relationality, what happens to those voices modified by electronic-digital processors? The article arises from a double positioning between neo-materialist theory and performative practice. Three nodes are investigated: the formation of unprecedented subjectivities that destitute the main dichotomies, the relationship with verbal language from a political-imaginative perspective, and the de-tuning capacities of the environmental acoustics created by these voices when taken collectively, tending to the making of themselves as instruments of pressure against environmental injustices.